KHULU' SEBUAH UPAYA MEMUTUSKAN IKATAN PERKAWINAN (STUDI KASUS DI PENGADILAN AGAMA GARUT) - Qisthy Fajriyanti; Diana Farid; Muhammad Husni Adulah Pakarti; Aceng Hobir; Moh Imron Taufik (Al-Adl : Jurnal Hukum, 2023)
This research aims to find out (1) why the husband's violation of taklik talaq becomes one of the divorces decided as a matter of khulu. (2) What considerations form the basis of the judge in accepting and deciding on the khulu' case and (3) The legal consequences arising from divorce by way of khulu. The research method used is qualitative by conducting interviews to obtain the necessary information. The data sources used were obtained from the Garut Religious Court in the form of documents and data related to this research. Based on the study's results, it was found that the reason for taklik talak being part of khulu' cannot be separated from the history of taklik talak being enforced as part of an effort to prevent the husband's arbitrariness. Next, in accepting and breaking up the divorce by way khulu cannot be separated from the suitability of the lawsuit filed, and in a divorce by way of the khulu', the opinion of the judge in his decision will be influenced by the willingness of the wife in the amount of iwadh to be paid. Implementation of divorce khulu also has inherent consequences, namely the enactment of the iddah period and there is no reconciliation except with a new contract, the obligation to pay iwadh by the wife, and the loss of the husband's obligation to provide iddah and mutʼah.